Inhibition of N-type Ca2+ channels ameliorates an imbalance in cardiac autonomic nerve activity and prevents lethal arrhythmias in mice with heart failure. (5th August 2014) - Yamada, Yuko; Kinoshita, Hideyuki; Kuwahara, Koichiro; Nakagawa, Yasuaki; Kuwabara, Yoshihiro; Minami, Takeya; Yamada, Chinatsu; Shibata, Junko; Nakao, Kazuhiro; Cho, Kosai; Arai, Yuji; Yasuno, Shinji; et al.
Abstract: Aims: Dysregulation of autonomic nervous system activity can trigger ventricular arrhythmias and sudden death in patients with heart failure. N-type Ca 2+ channels (NCCs) play an important role in sympathetic nervous system activation by regulating the calcium entry that triggers release of neurotransmitters from peripheral sympathetic nerve terminals. We have investigated the ability of NCC blockade to prevent lethal arrhythmias associated with heart failure. Methods and results: We compared the effects of cilnidipine, a dual N- and L-type Ca 2+ channel blocker, with those of nitrendipine, a selective L-type Ca 2+ channel blocker, in transgenic mice expressing a cardiac-specific, dominant-negative form of neuron-restrictive silencer factor (dnNRSF-Tg). In this mouse model of dilated cardiomyopathy leading to sudden arrhythmic death, cardiac structure and function did not significantly differ among the control, cilnidipine, and nitrendipine groups. However, cilnidipine dramatically reduced arrhythmias in dnNRSF-Tg mice, significantly improving their survival rate and correcting the imbalance between cardiac sympathetic and parasympathetic nervous system activity. A β-blocker, bisoprolol, showed similar effects in these mice. Genetic titration of NCCs, achieved by crossing dnNRSF-Tg mice with mice lacking CACNA1B, which encodes the α1 subunit of NCCs, improved the survival rate. With restoration of cardiac autonomic balance, dnNRSF-Tg; CACNA1B +/− mice showed fewer malignant arrhythmias than dnNRSF-Tg; CACNA1B +/+ mice. Conclusions: Both pharmacological blockade of NCCs and their genetic titration improved cardiac autonomic balance and prevented lethal arrhythmias in a mouse model of dilated cardiomyopathy and sudden arrhythmic death. Our findings suggest that NCC blockade is a potentially useful approach to preventing sudden death in patients with heart failure.